THE INFLUENCE OF LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE SUB-DISTRICT OFFICE - Nurse Saragih; Lizbet E. Butar -Butar; Diana F. Butar-butar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Objective study This is For know influence leadership to performance employee , discipline Work to performance employee as well as For know influence leadership and discipline Work in a manner simultaneous to performance employee at the District Head Office . Study This is carried out at the District Head Office , p This aim For know performance civil servants at the District Head Office . For population and sample researcher take whole Main employees at the Raya sub-district office, totaling 30 respondents. Leadership own influence positive on the Performance of Employees of the Raya District Office . reality This proven with statistical test results Where t table value of 0.05 compared with t value count For variable leadership 9.019. Comparison results the showing that t value count > t table ie 9.019 > 0.05 then Ho is rejected and Ha is accepted . Discipline Work own influence negative to performance Office Employee District Head . Reality This proven with Where are the statistical test results t table value of 0.05 compared with t value count For variable discipline work -0.274. Comparison results the showing that t value count > t table namely -0.274 > 0.05 then Ho is rejected and Ha is accepted. Results from study This conclude that in a manner partial , variable leadership No significant to performance employee . Different with variable discipline influential work _ significant to performance District Head Office Officer . kindly simultaneously , leadership and discipline Work influential on employee performance .